Fanaticism and Consumptive Behavior Among Players of The Otome Game Love and Deepspace - Hikarin Aadea Magfiroh; Onny Fransinata Anggara (Lembaga Intelektual Muda (LIM) Maluku, 2026)
The expansion of digital gaming has transformed mobile games into psychological and economic spaces that shape players’ emotions and consumption behavior. Otome games, characterized by romantic narratives and intense emotional interaction, exemplify this shift. This study investigates the relationship between fanaticism and consumptive behavior among players of the otome game Love and Deepspace. Using a quantitative correlational design, data were collected from 100 active players with a minimum of one year of gameplay experience. Instrument validity was assessed through expert judgment and statistical testing, while reliability was confirmed using Cronbach’s Alpha. Due to non-normal data distribution, Spearman’s rho correlation was employed for analysis. The results reveal a positive and significant relationship between fanaticism and consumptive behavior (ρ = 0.583, p < 0.001), indicating a moderate correlation. These findings suggest that emotional attachment, immersive gameplay, and romantic interactions with virtual characters encourage players to engage in in-game spending. This study provides empirical evidence that emotional fanaticism toward virtual characters acts as a pivotal catalyst for repetitive in-game spending. It highlights how the character-centered narrative architecture of otome games effectively reconfigures digital consumption behavior among players